Rehabilitation Programs for Incarcerated Drug Offenders in Malaysia: Experience-Based Perspectives on Reintegration and Recidivism. (March 2020) - Cheah, Phaik Kin; Unnithan, N. Prabha; Raran, Annie Margaret Sandela
This study explores lived experiences of repeat drug offenders in Malaysia, their reasons for recidivating, and related shortcomings in prison rehabilitation programs. We categorize the prisoners' descriptions and interpretations of their experiences after participating in rehabilitation programming. We are able, as a result, to shed light on these offenders' perspectives on the treatment efforts in which they were involved.